Exceptional Visible‐Light‐Driven Cocatalyst‐Free Photocatalytic Activity of g‐C3N4 by Well Designed Nanocomposites with Plasmonic Au and SnO2. Issue 21 (1st August 2016) - Zada, Amir; Humayun, Muhammad; Raziq, Fazal; Zhang, Xuliang; Qu, Yang; Bai, Linlu; Qin, Chuanli; Jing, Liqiang; Fu, Honggang
Abstract : In this work, plasmonic Au/SnO2 /g‐C3 N4 (Au/SO/CN) nanocomposites have been successfully synthesized and applied in the H2 evolution as photocatalysts, which exhibit superior photocatalytic activities and favorable stability without any cocatalyst under visible‐light irradiation. The amount‐optimized 2Au/6SO/CN nanocomposite capable of producing approximately 770 μmol g −1 h −1 H2 gas under λ > 400 nm light illumination far surpasses the H2 gas output of SO/CN (130 μmol g −1 ), Au/CN (112 μmol g −1 h −1 ), and CN (11 μmol g −1 h −1 ) as a contrast. In addition, the photocatalytic activity of 2Au/6SO/CN maintains unchanged for 5 runs in 5 h. The enhanced photoactivity for H2 evolution is attributed to the prominently promoted photogenerated charge separation via the excited electron transfer from plasmonic Au (≈520 nm) and CN (470 nm > λ > 400 nm) to SO, as indicated by the surface photovoltage spectra, photoelectrochemical I – V curves, electrochemical impedance spectra, examination of formed hydroxyl radicals, and photocurrent action spectra. Moreover, the Kelvin probe test indicates that the newly aligned conduction band of SO in the fabricated 2Au/6SO/CN is indispensable to assist developing a proper energy platform for the photocatalytic H2 evolution. This work distinctly provides a feasible strategy to synthesize highly efficient plasmonic‐assisted CN‐based photocatalysts utilized for solar fuel production. Abstract : Fabricated plasmonic Au/SnO2 /g‐C3 N4 nanocomposites exhibit superior photocatalytic activities without any cocatalyst under visible‐light irradiation. The key lies in the newly aligned conduction band of SnO2, by which a proper energy platform is provided for the effective charge transfer from plasmonic Au and g‐C3 N4 and then to energetically induce H2 ‐evolution reaction.